Exopolysaccharide composition and size in Sulfolobus acidocaldarius biofilms - Kuschmierz, Laura; Meyer, Martin; Bräsen, Christopher; Wingender, Jost; Schmitz, Oliver J.; Siebers, Bettina (Frontiers in Microbiology, 2022)
Extracellular polymeric substances (EPS) comprise mainly carbohydrates, proteins and extracellular DNA (eDNA) in biofilms formed by the thermoacidophilic Crenarchaeon Sulfolobus acidocaldarius. However, detailed information on the carbohydrates in the S. acidocaldarius biofilm EPS, i.e., the exopolysaccharides (PS), in terms of identity, composition and size were missing. In this study, a set of methods was developed and applied to study the PS in S. acidocaldarius biofilms. It was initially shown that addition of sugars, most significantly of glucose, to the basal N-Z-amine-based growth medium enhanced biofilm formation. For the generation of sufficient amounts of biomass suitable for chemical analyses, biofilm growth was established and optimized on the surface of membrane filters. EPS were isolated and the contents of carbohydrates, proteins and eDNA were determined. PS purification was achieved by enzymatic digestion of other EPS components (nucleic acids and proteins). After trifluoroacetic acid-mediated hydrolysis of the PS fraction, the monosaccharide composition was analyzed by reversed-phase liquid chromatography (RP-LC) coupled to mass spectrometry (MS). Main sugar constituents detected were mannose, glucose and ribose, as well as minor proportions of rhamnose, N acetylglucosamine, glucosamine and galactosamine. Size exclusion chromatography (SEC) revealed the presence of one single PS fraction with a molecular mass of 4-9 x 104 Da. This study provides detailed information on the PS composition and size of S. acidocaldarius MW001 biofilms and methodological tools for future studies on PS biosynthesis and secretion.